Exchange-Rate-Based Stabilization : A Model of Financial Fragility - Sobolev, Yuri (IMF Working Papers; Working Paper ;, 2000)
Interactions between banks and open capital account are investigated as rationalizations for empirical regularities characterizing disinflation programs anchored by the exchange rate. The financial system is characterized by bank dominance and lending externality - banks do not internalize the effect of their lending on other banks' information about potential borrowers. Model dynamics simulation shows that remonetization in the wake of disinflation increases loanable funds supply and translates into bank credit expansion financed by capital inflows. A credit-driven boom results, accompanied by overvaluation and current account deficits generating financial fragilities and vulnerability to a shock that can trigger banking and balance-of-payments crises.